Sociological Implications of the Acquisition of the Fante Language by Northern Ghanaian Immigrants in the Sekondi-Takoradi Metropolis (Mediterranean Journal of Social Sciences, 2024)
The phenomenon of language acquisition among immigrant populations carries significant sociological implications, particularly in multicultural societies where linguistic diversity is prevalent. There are lots of northern Ghanaian immigrants living and working in the Sekondi-Takoradi Metropolis. The acquisition of the Fante language by the immigrants presents interesting socio-linguistic ramifications worthy of scholarly attention. Data was gathered using semi-structured interviews, which were audio-recorded and transcribed verbatim. Data was processed using atlas and analyzed using a thematic analysis approach. The study concluded that immigrants who worked in the markets or stayed in Effiakuma acquired the language faster than those who worked in the formal sector where interaction was largely done in English. Also, the paper concluded with the observation that there are acquisition challenges with the Fante language; and that there is some sociological importance of the language to the immigrants which include commercial, security, amorous relationship and liturgical needs. It was recommended that the Sekondi Takoradi Municipality implement language learning programs specifically tailored to northern Ghanaian immigrants in Effiakuma, focusing on teaching them the Fante language. These programs should be easily accessible and provide comprehensive language instruction to enhance social integration, economic opportunities, cultural preservation, and personal security for the immigrants Received: 19 February 2023 / Accepted: 27 December 2023 / Published: 5 January 2024